Defensins: transcriptional regulation and function beyond antimicrobial activity - Contreras, Gabriela; Shirdel, Iman; Braun, Markus S.; Wink, Michael (Developmental & comparative immunology, 2020)
Defensins are one the largest group of antimicrobial peptides and are part of the innate defence. Defensins are produced by animals, plants and fungi. In animals and plants, defensins can be constitutively or differentially expressed both locally or systemically which confer defence before and a stronger response after infection. Immune signalling pathways regulate the gene expression of defensins. These pathways include cellular receptors, which recognise pathogen-associated molecular patterns and are found both in plants and animals. After recognition, signalling pathways and, subsequently, transcriptional factors are activated. There is an increasing number of novel functions in defensins, such as immunomodulators and immune cell attractors. Identification of defensin triggers could help us to elucidate other new functions. The present article reviews the different elicitors of defensins with a main focus on human, fish and marine invertebrate defensins.